2019
DOI: 10.1186/s13578-019-0346-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 over-expression inhibited Th17 cell differentiation to relieve endometriosis through miR-342-3p/IER3 pathway

Abstract: Objective To investigate the mechanism of LncRNA H19 in Th17 cell differentiation and endometrial stromal cells (ESCs) proliferation in endometriosis (EMS). Methods LncRNA H19, miR-342-3p and IER3 expressions were detected by qRT-PCR and western blot. The percentage of Th17 cells/CD4+ T cells was detected by flow cytometry. IL-17 level was measured by ELISA. The interaction of miR-342-3p and IER3 was confirmed by Luciferase reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…This is accompanied with an increase in miR-342-3p levels. This miRNA binds with the 3 ′ UTR of IER3, thus inhibiting its expression (93). IER3 participates in proteasomal degradation of IF-1.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is accompanied with an increase in miR-342-3p levels. This miRNA binds with the 3 ′ UTR of IER3, thus inhibiting its expression (93). IER3 participates in proteasomal degradation of IF-1.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
“…In addition, Xu et al have demonstrated the role of the estrogen-modulated H19/ACTA2/miR-216a-5p axis in the regulation of invasion and migration of eutopic endometrial stromal cells in subjects with endometriosis ( 78 ). Liu et al have reported the significance of H19/miR-342-3p/IER3 axis in suppression of Th17 cell differentiation and decreasing the risk of endometriosis ( 93 ). A recent high throughput study of RNA profile of the ectopic and eutopic endometrium of patients has led to construction of the ceRNA network.…”
Section: Interaction Between Mirnas and Lncrnas In The Pathogenesis Omentioning
confidence: 99%
“…LncRNAs, a class of transcripts longer than 200 nucleotides with a limited or without protein-coding function, are involved in many diseases owing their modulating effect toward diverse biological processes, such as cell proliferation, apoptosis, and differentiation 17 . More importantly, many lncRNAs, such as lncRNA MEG3, lncRNA NEAT1, and lncRNA H19, have been proven to be tightly linked to Th7 cell differentiation 18 – 20 . Colorectal neoplasia differentially expressed (CRNDE), an lncRNA located on chromosome 16, is highly expressed in multiple cancers, and it plays indispensable roles in the development of different types of cancer, including CRC 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that lncRNA H19 is involved in the regulation of expression of many miRNAs. [21][22][23][24] Liu et al 25 stated that up-regulated lncRNA H19 participates in the regulation of proliferation and apoptosis of endometrial stromal cells (ESCs), so lncRNA H19 may be related to adenomyosis.…”
Section: Introductionmentioning
confidence: 99%